Asupan Gizi Anak Usia Dini Melalui Program Kerja Di Wilayah Kerja Puskesmas Tamalanrea Makassar - Nursiah, Andi; Mayasari, Eka; Fitri, Lidia; Kadir, Erni; Masdarwati, Masdarwati; Devin, Devin (Asosiasi Guru dan Dosen Seluruh Indonesia, 2024)
In Indonesia, nutritional problems, especially for early childhood, are a big problem because they are closely related to general health indicators such as morbidity and mortality rates. One effort to improve the level of public health can be done by improving the nutritional status of all family members with the support of various factors in a coordinated manner and is part of development to improve community welfare. The aim of efforts to improve nutritional status is to improve the nutritional condition of all members of society through participation and equal distribution of activities, changes in behavior that support the achievement of improved nutrition. Nutrition, which plays a big role in children's growth and development, must be a supervised and programmed part. Nutritional intake in early childhood cannot be separated and is closely related to children's health and intelligence. Apart from that, the nutritional intake the child receives will be a supporting factor in the child's growth and development. An unbalanced diet and inadequate or excessive nutritional intake can cause stunted growth and development in children. Monitoring of nutritional status is carried out every month in the Tamalanrea Community Health Center Work Area, there are 6 young children who have normal nutritional status and 18 young children still have malnutrition status, one of which is malnourished. Thirteen Early Childhood Children can no longer be monitored because they are not actively attending. The quality and quantity of complementary foods for breast milk really determines the nutritional status of young children. For this reason, mothers need to be given knowledge and skills in processing food by paying attention to the quality and quantity of complementary breast milk foods. Quality is seen from the type and diversity of food, while quantity is seen from the frequency of feeding. In connection with this, community service activities were carried out involving malnourished mothers of young children in making nutritious and varied complementary foods for breast milk.